14(t-5)+7=7(3t+2)-8

Simple and best practice solution for 14(t-5)+7=7(3t+2)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14(t-5)+7=7(3t+2)-8 equation:



14(t-5)+7=7(3t+2)-8
We move all terms to the left:
14(t-5)+7-(7(3t+2)-8)=0
We multiply parentheses
14t-(7(3t+2)-8)-70+7=0
We calculate terms in parentheses: -(7(3t+2)-8), so:
7(3t+2)-8
We multiply parentheses
21t+14-8
We add all the numbers together, and all the variables
21t+6
Back to the equation:
-(21t+6)
We add all the numbers together, and all the variables
14t-(21t+6)-63=0
We get rid of parentheses
14t-21t-6-63=0
We add all the numbers together, and all the variables
-7t-69=0
We move all terms containing t to the left, all other terms to the right
-7t=69
t=69/-7
t=-9+6/7

See similar equations:

| 5-8x=2x-15 | | X=13+(-2y) | | 5x+13-20=8x+14 | | 18=r/3+15 | | 20=-6u+4(u+4) | | 1/x+1/5x=4/24 | | 11x+5-3x=8x-2+7 | | (8x-3)=(16x-33) | | d=6.6d | | 11x+5-3x=8x-2-7 | | 34x−80=10x−8 | | -10−d=10+3d | | x/11-3=3/22 | | x/11-3=3/12 | | -19=z/4+-26 | | 1/2x=45x | | 12=3(y+6)-5y | | -5(2x+6)=2(2x-1) | | 4(v+8)=84 | | 0x+3=5x+2 | | x-(-27)=19 | | 5w+3w=3w+9 | | -52-9x=109+9x | | d/4-15=18 | | -33=9-7k | | d/4-15=29 | | w/3+-3=1 | | 1/3+z=8/9 | | r2− -8=9 | | 2x-3+2x-3=x | | 21x+66=90 | | X+20=3/2(x/2+20) |

Equations solver categories